Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. Ethical leadership and role of in managing organizational change "Analytical study" Asst-Prof. Mofleh Hamed Alsulami 2. A proposed model for applying the Analytical Procedures Auditing Standard (No. 520) to measure the creditworthiness of customers (Applied to Alawwal Medical Laboratories customer account balances for the year 2021) Dr. Alfateh Alamin Abdalrahim, Mr. Abd Elhaq Maki Elhadi 3. The Role of Idea Generation in Enhancing the Relationship Between Strategic Orientation and Entrepreneurial Performance: A Field Study of a Sample of Industrial Production Companies in Khartoum State Co-Prof. Elsheikh Mohammed Elkhidir, Asst-Prof. Basheer Eltahir Basheer, Mr. Helmi Mohamed Nsibi , Dr. Anis Mohammed Souissi 4. Analysis of the impact of strategic diversification on corporate performance in the global competitive market Dr. Sadiq Ali Mubarak Al-Shuwaikhat, Dr. Haya Ibrahim Abdulrahman Al Tuwaym, Dr. Sara Saad Al-Dawsari 5. The United States of America: Comprehensive Support for Israel in its War on Gaza Mr. Akram Mohammad Ali Chamas 6. The Impact of The Marketing Mix on The Development of Banking Services in the Financial Investment Bank Dr. Ashwag Sied Ali Ibrahim 7. Classification of banks based on the financial recovery index using discriminant analysis by applying it to a sample of banks registered on the Amman Stock Exchange for the period (2000-2021) Teacher / Rawaa Ahmad Yousef